FORMULATION AND IN VITRO CHARACTERIZATION SOLID SELF EMULSIFYING DRUG DELIVERY SYSTEM OF RAMIPRIL PREPARED BY ADSORPTION TECHNIQUE - K., Madhavi; A., Shikha; B., Suresh (International Journal of Current Pharmaceutical Research, 2016)
Objective: The primary goal of the present work was to formulate solid self-emulsifying drug delivery systems (S-SEDDS) in order to improve the solubility of the highly lipophilic antihypertensive drug, ramipril. Methods: SEDDS are generally liquid form preparations obtained by homogeneously mixing oils, surfactants and co-surfactants along with drug component. Based on solubility studies Capmul PG8 NF, Gelucire 44/14 and Transcutol P were selected as oil, surfactant, co-surfactant respectively in order to prepare liquid SEDDS (L-SEDDS). Nine different liquid SEDDS were prepared and subjected to various evaluation tests in order to obtain optimized L-SEDDS. Finally, the optimized formulation was converted to S-SEDDS by physical adsorption technique using an inert carrier. Further, S-SEDDS were also subjected to solid state characterization. Results: Out of 9 different L-SEDDS, S9 formulation was optimized as it formed thermodynamically stable emulsion without any drug precipitation and phase separation on storage and also showed least globule size (22.56 nm). The optimized formulation was loaded onto inert carrier (Sylysia FCP 350) to obtain S-SEDDS. S-SEDDS showed acceptable flow properties. They were further processed for solid state characterization such as XRD, DSC and SEM and the results confirmed the transformation of native crystalline nature of drug to an amorphous state. FTIR analysis also confirmed no drug-excipient interaction. S-SEDDS showed improved in vitro dissolution behaviour of ramipril over that of pure drug. Conclusion: Ramipril S-SEDDS retained emulsification characteristics of L-SEDDS. Further, S-SEDDS was encapsulated in hard gelatin capsules and this formulation proved to have improved solubility for ramipril.